Diagnostic Accuracy of Magnetic Resonance Imaging in Detecting the Severity of Abnormal Invasive Placenta: A Systematic Review and Meta-Analysis. Issue 1 (March 2019) - Familiari, A.; Liberati, M.; Lim, P.; Pagani, G.; Cali, G.; Buca, D.; Manzoli, L.; Flacco, M.E.; Scambia, G.; D'antonio, F.
Abstract : ( Acta Obstet Gynecol Scand . 2018;97:507–520) As cesarean delivery rates have increased in many countries, a marked rise in the prevalence of abnormal invasive placenta (AIP) has also occurred. Accurate prenatal diagnosis of AIP can significantly reduce maternal morbidity associated with this disorder by allowing for preoperative planning of obstetric and anesthetic management. Ultrasound is considered the primary tool to diagnose AIP; but in cases where ultrasound examination is inconclusive, prenatal magnetic resonance imaging (MRI) may be performed. The current authors have previously found MRI to have good diagnostic accuracy for identifying AIP based on a systematic review and meta-analysis. This systematic review and meta-analysis was undertaken with the primary aim of evaluating the diagnostic accuracy of prenatal MRI for detecting the severity of AIP, as determined by the depth and topography of placental invasion, in women with risk factors for AIP. The secondary goal of the study was to evaluate individual MRI signs for their predictive accuracy is assessing AIP severity.